Hopping conduction and random telegraph signal in an exfoliated multilayer MoS2 field-effect transistor. (13th January 2017) - Li, Lijun; Lee, Inyeal; Youn, Doo-Hyeb; Kim, Gil-Ho
Abstract: We investigate the hopping conduction and random telegraph signal caused by various species of interface charge scatterers in a MoS2 multilayer field-effect transistor. The temperature dependence of the channel resistivity shows that at low temperatures and low carrier densities the carrier transport is via Mott variable range hopping with a hopping length changing from 41 to 80 nm. The hopping conduction was due to electron tunneling through localized band tail states formed by the scatterers located in the vicinity of the MoS2 layer. In the temperature range of 40–70 K, we observed random telegraph signal (RTS) that is caused by the capture and emission of a carrier by the interface traps that are located away from the layer. These traps form strong potential that interact with the layer and change the potential profile of the electron system. The characteristics of RTS depend strongly on gate bias and temperature, as well as the application of a magnetic field.